Dampak Penggunaan Filter Instagram dan Tiktok Terhadap Citra Diri, Terutama Bagi Wanita - Millenia, Zahra; Hidayat, Taufik Wal (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
Advances in digital technology have changed the way individuals shape and project their self-image on social media, especially through the use of filters on platforms like Instagram and TikTok. This study aims to analyze the impact of the use of filters on women's self-image in psychological and social aspects. With a quantitative approach, data was collected through an online survey of 50 female respondents aged 18-30 years who actively used filters on social media. The results showed that 75% of respondents routinely used beauty filters to improve their visual appearance. As many as 60% of respondents feel more confident after using it. However, 40% of respondents experience dissatisfaction due to the difference between self-image on social media and reality, which leads to social anxiety and dissatisfaction with the body. Regression analysis showed a negative correlation between the intensity of filter use and confidence (coefficient -0.45; p=0.03), which indicates that the more frequent the filter use, the higher the risk of decreased confidence. The study gathered that the use of filters on social media can reinforce social pressure against unrealistic beauty standards, create a gap between online and offline identities, and increase the potential for self-satisfaction. Therefore, it is important to increase digital literacy and critical awareness of the psychological impact of using filters on social media.